Sub-tropical and tropical crops (Boca Raton, Florida, 1994)
All aspects of plant growth and development are influenced directly or indirectly by environmental variables. Environmental factors have a profound effect on plant phenotype and determine the extent to which genotypic is expressed. The book addresses an understanding of the response of crops to environmental variables (light, temperature, water, and salinity). The crops discussed in this book are the major commercial crops generally grown in subtropical or tropical climates
Keywords: tropical fruit - ecophysiology - handbooks, manuals, etc,fruit - ecophysiology - handbooks, manuals, etc